2021
DOI: 10.21037/atm-21-1100
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of hemodialysis plus hemoperfusion versus hemodialysis alone in adult patients with end-stage renal disease in China

Abstract: Background: This study evaluates the cost-effectiveness of hemodialysis (HD) plus hemoperfusion (HP) with HD alone in adult patients with end-stage renal disease (ESRD) in China.Methods: A Markov model was constructed to assess the cost-effectiveness of interventions over a lifetime horizon. Model parameters were informed by the HD/HP trial, the first randomized, open-label multicenter trial comparing survival outcomes and incidence of cardiovascular disease (CVD) for HD + HP versus HD alone, and supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…[19,20] In these circumstances, large clinical trials have demonstrated significant symptom reduction with improvement in quality of life in the group of patients treated with HA-HDx for at least one of the three sessions each week [21,22] and have led to the consideration that HA-HDx may represent a sustainable, cost-effective new frontier in chronic blood purification. [19][20][21][22][23] The logic and rationale behind the improvement is the high capacity of the sorbent to remove solutes in the mediumlarge molecular weight and even small protein-bound toxins responsible for the uremia retention syndrome. [7,24] We may therefore conclude that HA-HDx represents a viable option for chronic blood purification in those patients where classic dialysis techniques fail to achieve adequate correction of signs and symptoms and an acceptable quality of life.…”
Section: The Case Of Chronic Hemodialysismentioning
confidence: 99%
“…[19,20] In these circumstances, large clinical trials have demonstrated significant symptom reduction with improvement in quality of life in the group of patients treated with HA-HDx for at least one of the three sessions each week [21,22] and have led to the consideration that HA-HDx may represent a sustainable, cost-effective new frontier in chronic blood purification. [19][20][21][22][23] The logic and rationale behind the improvement is the high capacity of the sorbent to remove solutes in the mediumlarge molecular weight and even small protein-bound toxins responsible for the uremia retention syndrome. [7,24] We may therefore conclude that HA-HDx represents a viable option for chronic blood purification in those patients where classic dialysis techniques fail to achieve adequate correction of signs and symptoms and an acceptable quality of life.…”
Section: The Case Of Chronic Hemodialysismentioning
confidence: 99%
“…This is the first attempt at hepcidin clearance research by four dialysis modalities, HD, HDF, HD + HP, and HDF + HP until now. HD + HP had been proved to perform better than HD in improving the overall survival rates, cardiac function, cardiovascular events, and quality of life in MHD patients, 17 the cost‐effectiveness analysis suggested the HD/HDF + HP treatment should be cost‐effective for ESRD patients in China 18 . Our findings might not only help to further explain why the combined therapies are better than the HD/HDF alone but also supply novel therapy advice to improve anemia management in MHD patients.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…3 Though there are many RRT are available, the choice and adherence are based on the patient's financial background and affordability. 4 The term Pharmacoeconomics (PE) defined as "the studies that evaluates the behavior of individuals, firms, and markets relevant to the use of pharmaceutical products, services, and programs, and which majorly focuses on the costs (inputs) and consequences (outcomes) of that use. 5,6 The PE evaluations includes the Cost Minimization Analysis (CMA), Cost Effectiveness Analysis (CEA), Cost Utility Analysis (CUA), and Cost Benefit Analyses (CBA).…”
Section: Introductionmentioning
confidence: 99%